Economic analysis of distribution network planning considering decentralized energy storage system. Issue 1 (March 2021) - Lei, He; Sang, Zixia; Huang, Jiaqi; He, Jifeng; Yan, Jiong; Wang, Qixin; Yang, Dongjun; Du, Zhi; Wu, Lei
Abstract: The rapid development of renewable energy makes the power grid gradually change from traditional power system to high proportion renewable energy power system. The rapid development of electric vehicles, energy storage and controllable load increases the uncertainty of load. The flexible adjustable load is less, which can not meet the consumption demand of large wind and solar power generation, and can not support the power valley filling demand when the wind power output is insufficient. Energy storage system is very important for the safe and stable operation of renewable energy internet. How to consider the reliability and economy, this paper proposes a distribution network planning scheme considering energy storage system.